To bead or not to bead: A review of Pseudomonas aeruginosa lung infection models for cystic fibrosis - Reyne, Nicole; McCarron, Alexandra; Cmielewski, Patricia; Parsons, David; Donnelley, Martin (Frontiers in Physiology, 2023)
Cystic fibrosis (CF) lung disease is characterised by recurring bacterial infections resulting in inflammation, lung damage and ultimately respiratory failure. Pseudomonas aeruginosa is considered one of the most important lung pathogens in those with CF. While multiple CF animal models have been developed, many fail to mirror the CF lung disease of humans, including the colonisation by opportunistic environmental pathogens. Delivering bacteria to the lungs of animals in different forms is a way to model CF bacterial lung infections and disease. This review presents an overview of previous models, and factors to consider when generating a new P. aeruginosa lung infection model. The future development and application of lung infection models that more accurately reflect human CF lung disease has the potential to assist in understanding the pathophysiology of CF lung disease and for developing treatments.